Approximation of the classes $S^r_{p,θ}B(\mathbb{R}^d)$ of functions of many variables by entire functions of a special form - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Exact-order estimates are obtained for the approximations of the functional classes $S^r_{p,θ}B(\mathbb{R}^d)$ by entire functions of a special form.